The Effects of Vinpocetine on the Psychomotor Performances: Randomized clinical trial, single blind random clinical study. - Al-Kuraishy, Hayder; Al-Windy, Salahalduin; Algareeb, Ali I (Al-Nahrain Journal of Science, 2012)
Psychomotor performance parameters reflects the psychomotor and cognitive function in human being, these parameters includes TRT (total reaction time), RRT (recognition reaction time) and MRT (movement reaction time), also critical flickering fusion frequency (CFFF) which either ascending CFF or descending CFF. Vinpocetine drug is introduced in this study as single oral dose of 5mg and ten males medically students enrolled in this study, each subject do psychometric testing and after 2-3 hours of vinpocetine taken, the psychometric testing done. The results of this study showed significant effects (p<0.05) of this drug on TRT, RRT and descending CFF but insignificant effect on (p>0.05) movement reaction time (MRT) and ascending CFF. These consequences indicate a positive effect of vinpocetine on central nervous system but not on the peripheral nervous system.